Perencanaan Pembangunan Ekonomi Wilayah Berbasis Pertanian dalam Rangka Pengurangan Kemiskinan di Kalimantan Barat - Nia Permatasari; Dominicus Savio Priyarsono; Amzul Rifin (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2016)
Agriculture-based economic development planning is one of the efforts to reduce poverty in West Kalimantan by synergizing the performance of regional finance and agriculture sectors. The present study aimed at identifying relationship between the performance of regional finance, the performance of agriculture sector and poverty level of West Kalimantan. Analytical tools used to achieve the objectives of this research were descriptive statistics and panel data methods. The results show a positive relationship between the performance of regional finance and agriculture sectors. Gradual reallocation of agricultural budget can be an option for government to determine annual budget. Increase in preparatory investment and reallocation of regional government investment is a necessary policy to give allocation priority for agriculture sectors development. The agriculture sectors, in this case the segment of agriculture sectors on GRDP of West Kalimantan, negatively affect the poverty level. The development of agriculture sectors run by the government should be followed by the increase in human resources quality.